2018
DOI: 10.1007/s00167-018-4877-7
|View full text |Cite
|
Sign up to set email alerts
|

Posterior tibial slope impacts intraoperatively measured mid-flexion anteroposterior kinematics during cruciate-retaining total knee arthroplasty

Abstract: The data suggested that the choice of PTS had the greatest impact on the mid-flexion AP translation among the intraoperatively measured kinematics. This impact may be considered while making surgical decisions in the context of AP kinematics. When using a tibial component designed with "center" pivoting PTS, a surgeon may be able to fine tune the PTS to achieve proper mid-flexion AP stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Moreover, human cadaver specimens do not allow reproducible and comparable evaluations of different parameters due to the limited acquisition of samples and their decay. Lastly, clinical studies 3,8,10,19,22,28,56–59 are ethically limited, as extensive parameter studies into implant position and design are not possible.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, human cadaver specimens do not allow reproducible and comparable evaluations of different parameters due to the limited acquisition of samples and their decay. Lastly, clinical studies 3,8,10,19,22,28,56–59 are ethically limited, as extensive parameter studies into implant position and design are not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing tibial slope leads to a higher posterior translation of the femoral component in the early- to mid-flexion range (10°–70°), while slightly higher anterior femoral translation was found at higher flexion angles, thus reducing the amount of anterior-posterior translation, which is in excellent agreement with the cadaver study of Dai et al . 22 for the same load case. Contrarily, further studies 18,21,53,55 have reported continuous posterior translation due to increased tibial slopes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations